Diagnosing Immune Thrombocytopenia - Sachs, Ulrich J. (Hämostaseologie, 2019)
Although the detection of a characteristic autoantibody can prove immune thrombocytopenia (ITP), this diagnosis is often based on the exclusion of other causes of thrombocytopenia. Direct glycoprotein (GP)-specific tests have the property required to demonstrate such a characteristic autoantibody. In contrast, platelet-associated immunoglobulin G or antibody detection in plasma or serum is an insufficient diagnostic test. Moreover, data for commercial capture assays are sparse and their use is currently not recommended. A significant drawback of direct GP-specific tests is their low sensitivity, and a negative test result has no relevance. It is therefore also useful to establish a diagnosis of (primarily) hyperdestructive thrombocytopenia. A full blood count together with the immature platelet fraction has an excellent positive predictive value for ITP. Plasma glycocalicin has no apparent diagnostic value in identifying ITP patients, and conflicting data for TPO preclude its use for diagnostic purposes.
Keywords: platelet; diagnosis; autoantibodies